Accelerated weathering of bolted joints prepared from woven glass fiber-reinforced nanocomposites. (October 2019) - Chani, Kulwinder Singh; Saini, JS; Bhunia, H
This work deals with the accelerated aging of the bolted joints prepared from glass fiber-reinforced nanocomposite laminates. ASTM D5961 was used to design the bolted joint, and the geometric parameters, i.e. width-to hole-diameter ( W / D ) ratio and edge distance-to-hole diameter ( E / D ) ratio were fixed to 6 and 5, respectively. ASTM D1544 was used for accelerated aging, and a maximum of 500 h cyclical ultraviolet exposure, 8 h of ultraviolet radiation at 60 ℃ followed by 4 h of condensation at 50 ℃, was given to the specimens. A full factorial design of experiment was conducted on important control factors, i.e. aging time, bolt torque, and material variation, using response surface methodology. To investigate the effect of nanoclay content, a range of 0–5 wt% was investigated. Specimens with 3 wt% of nanoclay demonstrated optimum tensile strength and were selected to manufacture the bolted joint. Nanoplatelets having high aspect ratio increased the specific surface area and thus the tensile strength of the nanocomposite. It was found that the strength of the joints prepared with and without the nanoclay content decreased with the increase in the duration of aging. However, the joints with the nanoclay content had higher failure loads. The strength retention in the joints with nanoclay content was more in comparison to the joints made with neat epoxy. Nanoclay acted as a mechanical interlock at the fiber–matrix interface and improved the interfacial bond strength. A good dispersion of nanoclay also acts as a barrier to the moisture, which eventually reduces the degradation of the composite material due to the lesser fiber–matrix de-bonding under accelerated aging conditions.